PARTISIPASI POLITIK PEMILIH PEMULA DALAM PEMILIHAN LEGISLATIF TAHUN 2014 (Studi Pada Masyarakat Adat di Kelurahan Kulaba Kecamatan Pulau Ternate) - Hamis Basahona; Syahril Muhammad (Jurnal Geocivic, 2018)
This research is a study of the political participation of new voters in the 2014 legislative elections. The study of indigenous peoples is motivated by the use of local cultural symbols namely "Jou Kasa Ngom Kage" during legislative elections which refers to the obedience, and loyalty of indigenous peoples to the Sultan. The purpose of this research is (1) to find out the attractiveness of the beginner voters to the candidates who fight, (2) to find out the forms of political participation of first-time voters among indigenous peoples and (3) to find out the obstacles that hamper voter political participation beginners in the 2014 legislative elections. This type of research is qualitative research using observation, interview and documentation techniques. The results of this study indicate that (1) political participation of beginner voters in Kulaba sub-district, Ternate Island in the 2014 legislative elections, still tended to be dominated by the strength and attractiveness of charismatic traditional leaders. (2) the form of political participation of first-time voters in Kulaba Sub-District, Ternate Island as seen from involvement of novice voters in the dissemination of the stages of legislative elections, participation in campaign activities to deliver the vision and mission of political parties as well as the delivery of the vision and mission of candidates for legislative members and their presence in voting rights during elections and"Jou kasa ngom kage" (Ternate Malay) which means Jou'ou or Sultan where the people are there, this is the language of the press (media) which is trying to be manipulated by political actors in the run-up to the elections both legislative elections and Regional head elections with destination forget support from the community in the sultanate's cultural circle not a language that was born together with the birth of the kingdom of the sultan of Ternate. (3) constraints as a barrier to the participation of political voters in determining their voting rights are still influenced by the behavior of some legislative candidates who manipulate custom symbols for their political interests. Other than that there is still a lack of education level for novice voters who do not have a mature attitude in determining their choices as citizens who are free in determining their political choices. Keywords: Political Participation, Beginner Voter, Legislative Election and Kulaba Village